THE COUNTRYSIDE OF SVEČINSKE GORICE – WHO MAKES THE LANDSCAPE AND IN WHAT WAY? - Drozg, Vladimir (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
The purpose of this text is the geographical presentation of Svečinske gorice hills. We selected six thematic sections: natural disasters in the area, socio-demographic caracteristics of population, changes in cultural landscape, economic structure of the area, quality of living environment and phenomenon of nearby border. Several actors that built such regional caracteristics have been recognised and also several kinds of cooperation between them.